2020
DOI: 10.2147/cia.s248868
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safety of a Combined WB-EMS and High-Protein Diet Intervention in Sarcopenic Obese Elderly Men</p>

Abstract: Purpose: Whole-body electromyostimulation (WB-EMS) especially in combination with a high-protein supplementation has been established as an efficient treatment against sarcopenia. However, there are several case reports of rhabdomyolysis after WB-EMS application. Thus, we asked if this training could potentially lead to deteriorations of the cardiac as well as the renal function. Materials and Methods: One hundred sarcopenic obese men aged 70 years and older were randomly balanced (1-1-1) and allocated to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 73 publications
0
29
0
1
Order By: Relevance
“…Nevertheless, the combination of high intense exercise and increased protein doses might lead to negative renal (or cardiac) consequences [80,81]. So far, we have not addressed this issue in FrOST, a recent study we conducted on whole-body electromyostimulation (WB-EMS) and protein supplementation (1.7-1.8 g/kg/body mass/d) generated no negative effects in a similar cohort of men with sarcopenic obesity [82]. Thus, in summary we consider our intervention to be safe and applicable in this cohort of older men with musculoskeletal limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the combination of high intense exercise and increased protein doses might lead to negative renal (or cardiac) consequences [80,81]. So far, we have not addressed this issue in FrOST, a recent study we conducted on whole-body electromyostimulation (WB-EMS) and protein supplementation (1.7-1.8 g/kg/body mass/d) generated no negative effects in a similar cohort of men with sarcopenic obesity [82]. Thus, in summary we consider our intervention to be safe and applicable in this cohort of older men with musculoskeletal limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, post-training protein supplements did not demonstrate relevant substances regarding muscle mass increase, in relation to the elderly did not use this supplementation. On the other hand, other studies have observed a significant functional improvement in gait development and muscle strengthening, but not in increasing size and density (KEMMLER et al , 2020) .…”
Section: Discussionmentioning
confidence: 79%
“…In a study by Kemmler et al (2020), whole-body electrostimulation (WB-EMS), especially in combination with high protein supplements, was identified as an effective treatment for sarcopenia.…”
Section: Whole-body Electrostimulationmentioning
confidence: 99%
“…Studies show that this can be due to an improvement of its mitochondrial bioenergetic profile and decreased oxidative stress (BUONDONNO et al, 2020). Dietary supplementation of BCAAs in humans showed an association between the sea level of isoleucine, leucine and valine with lower risk of dementia; on the other hand the energy deficitprotein can accelerate the loss of muscle mass and its functions and considering the age factor we have what we call sarcopenia, and once diagnosed leads to risks of falls, disability, fragility, loss of independence and increased risk of death (BUONDONNO et al , 2020;KEMMLER et al , 2020) .…”
Section: Discussionmentioning
confidence: 99%